Acanthuridae in Bitunuris Waters Talaud Islands - Sasauw, Harpan; Bataragoa, Nego E.; Manu, Gaspar D.; Rondonuwu, Ari B.; Lalita, Jans D.; Kusen, Janny D. (Sam Ratulangi University, 2022)
This study aims to determine the species of fish from the Acanthuridae family in Bitunuris Village, Salibabu Island, Talaud Islands Regency. Fish samples were caught using monofilament gill nets with a mesh size of 1.5 inches, net length of 15 m, and net height of 2 m. Sampling was carried out in April and May 2021. A total of 63 individuals were caught consisting of nine species. Acanthurus nigrofuscus 40 individuals, 10.0-17.0 cm in length and 18-77 g in weight. Acanthurus lineatus three individuals, 9.4-17.7 cm in length and 17-96 g in weight. Acanthurus triostegus is seven individuals, 9.3-12.4 cm in length, and weighs 21-55 g. Acanthurus nigricans two individuals each measuring 13.9-13.9 cm in length and weighing 67-70 g each. One individual Ctenochaetus cyanocheilus, a total length of 10.3 cm, and weight of 29 g. Naso lituratus four individuals, length 15.1-17.7 cm and weight ranging from 68-115 g. Naso brevirostris one individual measuring 23.0 cm in length and weighing 186 g. One individual Naso brachycentron, 24.5 cm in length and 172 g in weight. Zebrasoma scopas four individuals, 12.1-15.8 cm in length and weighing 54-105 g.Keywords: Species, gill nets.AbstrakPenelitian ini bertujuan untuk mengetahui spesies ikan Famili Acanthuridae di Desa Bitunuris Pulau Salibabu Kabupaten Kepulauan Talaud. Sampel ikan ditangkap menggunakan jaring insang monofilamen dengan ukuran mata jaring 1,5 inci, panjang jaring 15 m, tinggi jaring 2 m. Pengambilan sampel dilakukan pada April dan Mei 2021. Sebanyak 63 individu yang tertangkap terdiri atas sembilan spesies. Acanthurus nigrofuscus 40 individu, panjang berkisaran 10,0-17,0 cm dan berat 18-77 g. Acanthurus lineatus tiga individu, panjang berkisaran 9,4-17,7 cm berat berkisaran 17-96 g. Acanthurus triostegus tuju individu, panjang 9,3-12,4 cm dan berat berkisaran antara 21-55 g. Acanthurus nigricans dua individu masing-masing ukuran panjang 13,9-13,9 cm berat masing-masing ukuran 67-70 g. Ctenochaetus cyanocheilus satu individu, panjang total 10,3 cm dan berat 29 g. Naso lituratus empat individu, ukuran panjang 15,1-17,7 cm berat berkisaran 68-115 g. Naso brevirostris satu individu ukuran panjang 23,0 cm memiliki berat 186 g. Naso brachycentron satu individu, panjang 24,5 cm dan berat 172 g. Zebrasoma scopas empat individu, panjang 12,1-15,8 cm dan berat 54-105 g.Kata Kunci: Spesies, jaring insang.